A stylistic study of the anthems of Herbert Howells together with a catalogue of the anthems and evening canticles - Mitchell, Mark Lanyon (College of Music, 2016)
This dissertation is divided into two sections. Section One: The biographical chapter gives a basic overview of Howells' life. Particular attention has been paid to teaching and church appointments, as the connection with the church was the main influence on his creative processes. This and other (direct or indirect) influences on Howells' creative process are discussed in the chapter following the Biography. The chapter on style focuses on Howells' technique of composition. As Howells acknowledged that Tudor music was a fundamental influence on his writing, aspects of his style that might have been particularly influenced are discussed. Very little analytical study of Howells' anthems has been undertaken to date. For the purpose of this dissertation, all the anthems have been studied and analysed in detail, but only a selection of works representative of his style have been used for the purpose of musical exemplification. Section Two: This section of the dissertation is a catalogue of the anthems and evening canticles. While researching in England, the author of this dissertation came across many manuscripts of sketches and incomplete anthems and evening canticles, but could find no published reference to these or catalogue including them. The author of this dissertation feel that it is important that these works be catalogued for reference purposes, which may prove to be of use in subsequent analytical studies of Howells' oeuvre.